The Effect of Economic Determinants on Capital Structure with Market Conditions as a Control Variable (Case Study of IDX-Listed LQ 45 Manufacturing Company in 2015-2019) - Theresalin Theresalin; I Gusti Ketut Agung Ulupui; Harya Kuncara (Syntax Corporation Indonesia, 2021)
This study was conducted to examine the effect of economic determinants on Capital Structure as measured by Profitability, Company Size, Company Growth, Asset Structure, Liquidity, Effective Tax Rate, Business Risk in LQ 45 Manufacturing Companies Listed on the IDX in the 2015 – 2019 Period. Used in this study was obtained from the Annual Report published to the public, either through the Indonesia Stock Exchange or the company's website. The sampling technique used is purposive sampling with a total sample of 135 samples. The data analysis technique used in this study is multiple linear regression analysis. Previously, the data has been tested with classical assumption testing, including descriptive analysis, chow test, Hausman test, LM test, data normality, heteroscedasticity, multicollinearity, and autocorrelation. During the observation period, it was shown that the research data were normally distributed. Based on the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, no variables deviated from the classical assumptions. This shows that the available data has met the requirements using the multiple linear regression equation models. This study indicates that the variables of Company Size, Company Growth, Effective Tax Rate, and Business Risk do not show a significant effect on capital structure. Profitability, Asset Structure, and Liquidity variables significantly affect capital structure.